The science to grow happy via stronger immunity (psychological perspectives) - Abdul Khaiyom, Jamilah Hanum (2020)
As one of the presenter for the webinar, I discussed on the Science to Grow Happy from the psychological perspectives. I discussed about the conception of happiness, bio-psycho-socio-spiritual contributing factors of happiness, what can we learn from the field of psychoneuroimmunology and it relationships with well-being, and some advises for health professionals to improve happiness and well-being of children.